System of Social Work in the Context of the Social Change in Lithuania - Švedaitė, Birutė (Acta Paedagogica Vilnensia, 2004)
In the article the question of function of social work in a modern society is discussed. The objectives and main areas of activity of social work are derived from there. The situation and the main problems of social work in Lithuania are presented and analysed. Theoretical background of the article is taken from the modern theory of social systems developed by the German sociologist Niklas Luhmann. Results can be formulated as follows: •Social work is a form in which modern society is responding to the fact that it has in generated a variety of needs. •The function of social work in a modern society is the organization of the secondary social security for individuals second. Social Work is engaged in the inclusion-exclusion problems in society. The aim of social work is to facilitate the participation of individuals in the most important systems of the society. •Social work in a modern society has three main tasks to fulfil: exclusion prevention, inclusion assistance, administration of exclusion. •Social work in Lithuania is a product of the social transformation process, and not the evolutionary development as in Western Europe. •Inadequate system of the primary social care in Lithuania prevents the development of the profession and the system of social work. •Social work is related to the monitoring and evaluation of the problematics of social inclusion and exclusion. In Lithuania, there is still a lack of skilled forces to describe the aid issue in the current society qualitatively. This explains the weaknesses of training of new social workers. •Due to the needs of social workers practice, the training of social workers in Lithuania requires a new conception.